Matematică
Andrei780
6

a) 2x + 1 supra 3 = -0, (6) b) 3x + 0,5 = -0,25 c) 0, 1 • x - 0, 25 = -0,34 d) (x-1) : 3 supra 4 = - 1 supra 6 e) 1 intregi 3 supra 7 -x = - 5 supra 14 f) 1 intregi 1 supra 3 •x - 0, (4) = (- 2 supra 3) totul la a 2 a

+0
(1) Răspunsuri
badeamarinela

a)2x+1 supra 3=-0,(6) rezulta x = -1supra2 b)3x+0,5=-0,25 rezulta x=-1supra4 c)0,1 * x-0,25=-0,34 rezulta x=-5,9 d)(x-1):3supra4=-1supra6 rezulta x=5supra6 e)1 intreg 3 supra 7-x=-5supra14 rezulta x=15 supra14 f)1 intreg1supra3 *x-0,(4)=(-2supra3)totul la a 2 a rezulta x=2supra3

Adaugă răspuns